Vegetation of Eurasia from the last glacial maximum to present: Key biogeographic patterns. (1st February 2017) - Binney, Heather; Edwards, Mary; Macias-Fauria, Marc; Lozhkin, Anatoly; Anderson, Patricia; Kaplan, Jed O.; Andreev, Andrei; Bezrukova, Elena; Blyakharchuk, Tatiana; Jankovska, Vlasta; Khazina, Irina; Krivonogov, Sergey; et al.
Abstract: Continental-scale estimates of vegetation cover, including land-surface properties and biogeographic trends, reflect the response of plant species to climate change over the past millennia. These estimates can help assess the effectiveness of simulations of climate change using forward and inverse modelling approaches. With the advent of transient and contiguous time-slice palaeoclimate simulations, vegetation datasets with similar temporal qualities are desirable. We collated fossil pollen records for the period 21, 000–0 cal yr BP (kyr cal BP; calibrated ages) for Europe and Asia north of 40°N, using extant databases and new data; we filtered records for adequate dating and sorted the nomenclature to conform to a consistent yet extensive taxon list. From this database we extracted pollen spectra representing 1000-year time-slices from 21 kyr cal BP to present and used the biomization approach to define the most likely vegetation biome represented. Biomes were mapped for the 22 time slices, and key plant functional types (PFTs, the constituents of the biomes) were tracked though time. An error matrix and index of topographic complexity clearly showed that the accuracy of pollen-based biome assignments (when compared with modern vegetation) was negatively correlated with topographic complexity, but modern vegetation was nevertheless effectively mapped by the pollen, despite moderate levels of misclassification for most biomes. The pattern at 21 ka is of herb-dominated biomes across the whole region. From the onset of deglaciation (17–18 kyr cal BP), some sites in Europe record forest biomes, particularly the south, and the proportion of forest biomes gradually increases with time through 14 kyr cal BP. During the same period, forest biomes and steppe or tundra biomes are intermixed across the central Asian mountains, and forest biomes occur in coastal Pacific areas. These forest biome occurrences, plus a record of dated plant macrofossils, indicate that some tree populations existed in southern and Eastern Europe and central and far-eastern Eurasia. PFT composition of the herbaceous biomes emphasises the significant contribution of diverse forbs to treeless vegetation, a feature often obscured in pollen records. An increase in moisture ca. 14 kyr cal BP is suggested by a shift to woody biomes and an increase in sites recording initialization and development of lakes and peat deposits, particularly in the European portion of the region. Deforestation of Western Europe, presumably related to agricultural expansion, is clearly visible in the most recent two millennia. Graphical abstract: Highlights: Pollen biomes for 1000-yr time slices from 21 to 0 ka BP are mapped for Eurasia. Tundra and steppe biomes dominated 21–14 ka BP, but forest biomes were also present. From 14 ka BP woody biomes expanded and wetland indicators became more prominent. Extensive taxon list underlines importance of forbs in glacial-age non-woody biomes. The grass-forb tundra biome maps European agricultural land in recent millennia.